Research on Dual Security Control for a Non-Linear CPS with Multi-Objective Constraints under DoS Attack and Actuator Fault: An Active-Passive Attack-Tolerant Approach - Li Zhao; Wei Li; Yajie Li (Journal of Control Science and Engineering)
Based on the discrete event-triggered communication scheme (DETCS), a codesign method of dual security control and communication for the non-linear cyberphysical system (CPS) with denial-of-service (DoS) attack and actuator fault is studied under multi-objective constraints. First, to effectively distinguish DoS attacks with different energy levels, the DoS attack detection method is established based on the maximum allowable delay of the system. Second, a non-linear CPS dual security control framework that integrates active-passive attack tolerance for DoS attack and active fault tolerance for actuator fault is constructed. Third, the low-energy DoS attack is regarded as a special kind of time delay, and a robust observer for the estimation of system states and actuator fault is designed, and a codesign method of passive attack tolerance, active fault tolerance, and communication is proposed. Furthermore, a correction compensation algorithm of control quantity is proposed for high-energy DoS attack based on the PID idea to make active-passive attack tolerance more effective. Finally, the effectiveness of the proposed method is verified by the simulation of a quadruple-tank model.